Development and validation of the Mental Health Promotion Scale. - Kadioglu, Hasibe; Karaca, Semra; Eren, Nurhan; Yurt, Seher (Perspectives in Psychiatric Care, 2022)
Purpose: This study aimed to develop and validate a scale that assesses adults' mental health promotion abilities. Design and Methods: This study was conducted in Istanbul from October 2016 to May 2018. Three rounds of the Delphi method were conducted to develop the scale. Findings: After the third Delphi round, the experts reached a consensus on 93 scale items. Forty‐six items were excluded from the scale based on exploratory factor analysis (EFA) results. In the last EFA of the 47‐item scale, a 12‐factor construct was found with an eigenvalue >1 that explained 64.3% of total variance. The overall Cronbach's alpha of the scale was.93. Practice Implications: This scale can be used to assess adults' mental health promotion abilities.